CircHGS enhances the progression of bladder cancer by regulating the miR-513a-5p/VEGFC axis and activating the AKT/mTOR signaling pathway. Issue 8 (18th April 2023) - Zhu, Yi; Zuo, Ling; Xiong, Hong; Li, Shihao; Chen, Ruiqi; Liu, Hongwei
ABSTRACT: Bladder cancer (BCa) is a malignant tumor that occurs in the bladder mucosa with high mortality. Circular RNAs (circRNAs), as newly discovered noncoding RNAs, are associated with the occurrence and development of BCa. However, the effects of circRNAs in BCa have not been fully elucidated. Through the GEO (Gene Expression Omnibus) database, an abnormally expressed circular RNA, circHGS (hsa_circ_0004721), was first identified in BCa. qRT – PCR was performed to measure the expression of circHGS in BCa tissues and cells. The intracellular localization of circHGS was detected by nucleocytoplasmic separation experiment and fluorescence in situ hybridization assay. In vitro experiments were conducted to detect the effects of circHGS on cell cycle, proliferation, migration and invasion. The correlations between miR-513a-5p and circHGS or VEGFC were confirmed by dual-luciferase reporter assay, qRT – PCR and western blot. The role of circHGS in vivo was verified by xenograft tumor mice model. In this study, we clarified the roles and potential mechanism of circHGS in BCa. CircHGS, originating from the HGS gene, is upregulated in BCa tissues compared to normal tissues. Moreover, the expression of circHGS in BCa was positively associated with tumor grade and pathological T stage. Functionally, silencing of circHGS apparently suppressed cell cycle, proliferation, migration and invasion, but circHGS overexpression showed the opposite result. In vivo experiments also suggested that knockdown of circHGS suppressed tumor growth. Mechanistically, circHGS functions as a sponge of miR-513a-5p to elevate VEGFC expression and activate the AKT/mTOR signaling pathway, ultimately promoting BCa progression. Our findings indicated that circHGS promotes BCa progression via the miR-513a-5p/VEGFC/AKT/mTOR pathway and can be a promising therapeutic target of BCa.